BANK CUSTOMER PROTECTION IN ACCOUNT BLOCKING FROM LEGAL PERSPECTIVE ON EXECUTION SEIZURE REQUESTS AND BANK SECRECY - Novyanti, Ni Wayan Regina; Kosasih, Prof. Dr. Johannes Ibrahim; Wesna, Dr. Putu Ayu Sriasih (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2024)
Banking business actors must maintain the level of health of their banks by applying the Precautionary Principle which is also directly related to the application of the Bank Secrecy Principle, which if the bank has neglected to apply the Bank Secrecy Principle, there is a potential loss that will be experienced by both customers and banking business actors themselves so that it can endanger the health of the bank itself. This study aimed to evaluate the legal protection for bank customers in the context of bank account blocking, with focus on the principles of bank secrecy. This study employed a normative legal methodology, using statutory and conceptual approaches. The data collection was conducted through library-based research. The findings indicated that according to the regulations stipulated in the Financial Services Authority Regulations (POJK) No. 1/2013 and No. 1/2014, bank customers who feel aggrieved have the right to file an internal complaint to the bank and seek resolution through dispute resolution. Moreover, bank customers are also allowed to file a lawsuit against the bank under Article 1365 of the Civil Code and file a lawsuit against an execution decision (verzet) as outlined in Article 195, Paragraph (6) of the Herzien Inlandsch Reglement (HIR) if the account blocking resulted from execution seizure request.